Munc13-1 Translocates to the Plasma Membrane in a Doc2B- and Calcium-Dependent Manner - Friedrich, Reut; Gottfried, Irit; Ashery, Uri (Frontiers in Endocrinology, 2013)
Munc13-1 is a presynaptic protein activated by calcium, calmodulin and diacylglycerols (DAG) that is known to enhance vesicle priming. Doc2B is another presynaptic protein that translocates to the plasma membrane (PM) upon elevation of internal calcium concentration ([Ca2+]i) to the submicromolar range, and increases both spontaneous and asynchronous release in a calcium-dependent manner. We speculated that Doc2B also recruits Munc13-1 to the PM since these two proteins have been shown to interact physiologically and this interaction is enhanced by Ca2+. However, this calcium-dependent co-translocation has never actually been shown. To examine this possibility, we expressed both proteins tagged to fluorescent proteins in PC12 cells and stimulated the cells to investigate the recruitment hypothesis using imaging techniques. We found that Munc13-1 does indeed translocate to the PM upon elevation in [Ca2+]i , but only when co-expressed with Doc2B. Interestingly, Munc13-1 co-translocates at a slower rate than Doc2B. Moreover, while Doc2B dislocates from the PM as soon as the [Ca2+]i returns to basal levels, Munc13-1 dislocates at a slower rate and a fraction of it accumulates on the PM. This accumulation is more pronounced under subsequent stimulations, suggesting that Munc13-1 accumulation builds up as some other factors accumulate at the PM. Munc13-1 co-translocation and accumulation was reduced when its mutant Munc13-1H567K, which is unable to bind DAG, was co-expressed with Doc2B, suggesting that Munc13-1 accumulation depends on DAG levels. These results suggest that Doc2B enables recruitment of Munc13-1 to the PM in a [Ca2+]i-dependent manner and offers another possible Munc13-1-regulatory mechanism that is both calcium- and Doc2B-dependent.